Home Care Dottoro’ta As a Development Program Smart City in Makassar City, Indonesia - Wahdania Suardi; Titin Purwaningsih; Ihyani Malik; Ahmad Taufik (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this article is to see the extent to which the Dottoro’ta home care is carried out as part of the smart city development program in Makassar City. The method used is a descriptive-qualitative approach which carries a literature study and uses the VOSviewer application in supporting dottoro’ta assembled research mapping. The result of this study is that the relationship between smart cities and technology is a support for the presence of Home Care Dottoro’ta in Makassar City. This is the latest innovation implemented in Makassar City. The home care service program or dottoro’ta is the first health service in Makassar that serves patients at the patient’s home, by calling service 112 and connected to the home care service or dottorot’ta. Services that are on standby and handled by professional health workers, help with adequate medical measures, administration of medicines according to the patient’s illness ambulance service refers to the hospital. By providing 48 units of Home Care cars complete with medical equipment placed in 46 Public Health Centers (PUSKESMAS) and health offices in Makassar City, it is a fairly helpful first step even though it is not optimal in facilities and infrastructure, especially makassar city has 16 sub-districts and related to Dottoro’ta is closely related to implementation, home care services, health service innovation, smart city, doctors and the best price. Tujuan artikel ini adalah untuk melihat sejauh mana terlaksananta home care Dottoro’ta sebagai bagian dari program pengembangan smart city di Kota Makassar. Metode yang digunakan adalah pendekatan deskriptif-kualitatif yang mana mengusung sebuah studi pustaka dan menggunakan aplikasi VOSviewer dalam mendukung pemetaan riset terakit Dottoro’ta. Hasil dari penelitian ini ialah keterkaitan smart city dengan tekhnologi menjadi pendukung hadirnya Home Care Dottoro’ta di Kota Makassar. Hal ini menjadi inovasi terbaru yang dilaksanakan di Kota Makassar. Program layanan home care atau dottoro’ta merupakan layanan kesehatan pertama di Makassar yang melayani pasien di rumah pasien, dengan menelpon ke layanan 112 dan dihubungkan pada layanan home care atau dottorot’ta. Layanan yang siaga dan ditangani oleh petugas kesehatan professional, pertolongan dengan tindakan medis memadai, pemberian obat obatan sesuai dengan penyakit pasien pelayanan mobil ambulance merujuk ke Rumah Sakit. Dengan menyediakan 48 unit mobil Home Care lengkap dengan perlatan medis yang di tempatkan di 46 Public Health Centers (PUSKESMAS) dan dinas kesehatan Kota makassar, menjadi langkah awal yang cukup membantu meskipun belum maksimal dalam sarana dan prasarana, terlebih kota makassar memiliki 16 kecamatan dan terkait dengan Dottoro’ta sangat erat kaitannya dengan, implementasi, layanan home care, inovasi layanan kesehatan, smart city, dokter dan harga terbaik.